Implicit and explicit learning strategies and fatigue: an evaluation of throwing task performance - Banihosseini, Reihaneh; Abdoli, Behrouz; Kavyani, Maryam (Frontiers in Psychology, 2025)
IntroductionThis study aimed to determine the effects of implicit (errorless) and explicit (errorful) training strategies on a throwing task under physiological and mental fatigue conditions.MethodsThirty-two participants, equally divided between the explicit and implicit learning groups, participated in a throwing task. The explicit learning group began at a significant distance from the target and gradually moved closer. In contrast, the implicit learning group started close to the target and progressively increased their distance. The initial session referred to as the acquisition phase, comprised 150 throws from five different distances. Subsequent sessions included a retention test and two transfer tests conducted under conditions of both physiological and mental fatigue. Mental fatigue was induced using a 30-minute color-word Stroop task, while physical fatigue was elicited by requiring subjects to maintain 50% of their maximum voluntary isometric contraction (MVC) in elbow extension for a 2-minute duration.ResultsThe results revealed that the implicit learning group exhibited improved performance under fatigue conditions and outperformed the explicit learning group significantly, regardless of the type of fatigue.ConclusionThis results suggests that implicit learning may improve motor performance even under fatigue conditions.